EFFICIENCY OF NITROGEN AND POTASSIUM APPLICATION ON PHYTOTECHNICAL PARAMETERS AND YIELD OF MELON - Alencar Fernandes, Pablo Cristovao de; Pereira, Laercio da Silva [UNESP]; Goncalves de Souza Lima, Carlos Jose; Silva Junior, Gabriel Barbosa da; Silva Santos, Theuldes Oldenrique da; Moura, Regiana dos Santos; Silva, Everaldo Moreira da (Univ Federal Uberlandia, 2020)
Phytotechnical parameters, yield and fertilizer use efficiency are relevant to the rational management of fertigation, especially in cultivation of high technological level. Thus, the objective was to evaluate the influence and efficiency of nitrogen (N) and potassium (K) application on the phytotechnical parameters, yield and nutritional efficiency of yellow melon in a fertigation system. The experiment was conducted in the city of Bom Jesus-PI, Brazil, from January to April 2016, in a strip-block design with four replicates, and the treatments consisted of five N levels ( 0, 45, 90, 135 and 180 kg ha(-1) in the form of urea) and five K levels (0, 60, 120, 180 and 240 kg ha(-1) in the form of potassium chloride), applied through fertigation. Collar diameter, main branch length, leaf chlorophyll content, number of leaves, leaf area index, biomass accumulation, fruit yield, and N and K use efficiencies were evaluated. Applications of 180 kg ha(-1) of N and 240 kg ha(-1) of K, respectively, led to the highest growth of the melon, while maximum production was obtained with the use of 112.50 and 165 kg ha(-1) of N and K, respectively. The efficiency of N and K use decreased with increasing levels.
Keywords: Cucumis melo; Fertigation; Fertilizer use efficiency